2015
DOI: 10.1007/s10554-015-0822-8
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between blood pressure variability, obesity and left atrial phasic function in hypertensive population

Abstract: We sought to investigate the relationship between blood pressure (BP) variability and left atrial (LA) phasic function assessed by volumetric and speckle tracking method in normal-weight, overweight and obese hypertensive patients. This cross-sectional study included 164 untreated hypertensive subjects who underwent a 24-h ambulatory BP monitoring and complete two-dimensional echocardiographic examination (2DE). All the patients were separated into three groups according to their body mass index (BMI): normal-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 25 publications
4
9
0
4
Order By: Relevance
“…However, in clinical practice, we do not routinely assess the different components of LA function, although this is now possible because of advances in noninvasive imaging techniques. Recent studies based on tissue Doppler imaging [9], vector velocity imaging (VVI) [10,11], or speckle tracking imaging (STE) [12][13][14][15][16] assessed LA function in patients with HTN with or without LV hypertrophy. However, literature data concerning LA strains in patients with HTN are conflicting.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in clinical practice, we do not routinely assess the different components of LA function, although this is now possible because of advances in noninvasive imaging techniques. Recent studies based on tissue Doppler imaging [9], vector velocity imaging (VVI) [10,11], or speckle tracking imaging (STE) [12][13][14][15][16] assessed LA function in patients with HTN with or without LV hypertrophy. However, literature data concerning LA strains in patients with HTN are conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…However, literature data concerning LA strains in patients with HTN are conflicting. Left atrial reservoir function has been shown to be reduced [12,13] or normal in patients with LV hypertrophy [10,11], whereas it showed early impairment in some studies of HTN patients without hypertrophy [14][15][16]. LA conduit function has been more consistently shown to be reduced, regardless of LV mass [9][10][11]13,15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…У пациентов с ожирени-ем имеется ряд особенностей суточного профиля ар-териального давления (АД) [4][5][6][7][8][9], которые обуслов-ливают повышение сердечно-сосудистого риска.…”
Section: Hypertension and Obesity артериальная гипертония и ожирениеunclassified
“…Tadic M. с соавт. [5] выяви-ли, что у нелеченных пациентов с АГ (n=164) при на-личии у них ожирения, в отличие от больных с АГ без ожирения, имеют место более высокие значения сред-несуточной, среднедневной и средненочной вариа-бельности. Нами также была выявлена достоверно большая вариабельность систолического АД (САД) в ночное время у больных среднего возраста с нелечен-ной АГ и ожирением, в сравнении с пациентами с АГ без ожирения [6].…”
Section: особенности суточного профиля артериального давления и патогunclassified